Attention, attention! Posttraumatic stress disorder is associated with altered attention-related brain function - Ely, Samantha L.; Zundel, Clara G.; Gowatch, Leah C.; Evanski, Julia M.; Bhogal, Amanpreet; Carpenter, Carmen; Shampine, MacKenna; Marusak, Hilary (Frontiers in Behavioral Neuroscience, 2023)
Posttraumatic stress disorder (PTSD) is a debilitating condition characterized by altered arousal, mood, and cognition. Studies report attentional alterations such as threat bias in individuals with PTSD, though this work has largely been conducted within emotionally-charged contexts (e.g., threatening stimuli). Emerging behavioral evidence suggests that PTSD-related attention deficits exist even in the absence of threatening cues or anxiety triggers. However, the role and functioning of attention brain circuits as they relate to PTSD remains underexplored. In this mini review, we highlight recent work using non-emotional stimuli to investigate the neurobiology of attention and disruptions to attention-related brain functioning among individuals with PTSD. We then discuss gaps in the current literature, including questions pertaining to the neural circuitry of attentional alterations in PTSD, as well as the contributions that trauma exposure, PTSD symptoms, comorbidities, and pre-existing vulnerabilities may have in this relationship. Finally, we suggest future directions for this emerging area of research, which may further inform knowledge surrounding the neurobiological underpinnings of PTSD and potential treatments.